Association of maternal serum homocysteine level with severity of preeclampsia: a case control study - Yelikar, Kanan Avinash; Deshpande, Sonali Satish; Kulkarni, Manisha Laxmikant (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The objective of the study was to investigate plasma levels of homocysteine in women with preeclampsia and eclampsia, and to assess whether there is any association between hyperhomocysteinemia and the severity of preeclampsia. Methods: In this case control study, 120 women were recruited in the study in which 40 cases of preeclampsia, 40 cases of eclampsia and 40 healthy normotensive women were taken as controls between the study period September 2013 to August 2015. Assessment of homocysteine level was done in cases and controls. Association was studied between maternal homocysteine level and preeclampsia and eclampsia and also with the severity of pre-eclampsia. Results: There was a significant association between pre-eclampsia and eclampsia and maternal serum homocysteine levels (median homocysteine level 16.25moμl/lit with P-value being less than 0.001 for preeclampsia ; median homocysteine level-31.34 μmol/lit with p value being less than 0.001 for eclampsia). There was also a significant association between severity of preeclampsia and maternal homocysteine level (mean serum homocysteine level in nonsevere preeclampsia 14.99±3.47 μmol/lit with p value being 0.35; in severe preeclampsia 19.90±6.17 μmol/lit with p value less than 0.001 and 30.44±4.75 μmol/lit with p value less than 0.001. Conclusions: In the present study a positive association was found between pre-eclampsia and maternal serum homocysteine levels and it was found to be statistically significant. Also the levels were higher as the severity of preeclampsia increased.